La cohésion grammaticale en langue française au discours de la parole Emmanuel Macron - Umam, Khotibul; Urip, Sri Rejeki; Joko, Bernadus Wahyudi (Digital Press Social Sciences and Humanities, 2019)
The language has an ideational function, which means that the language can be used as a tool to express ideas to others. One of forms of ideas that can be used in the language is the speech discourse. In general, the speech is organized in a clear structure. A well-formed speech must have two essential elements, cohesion and coherence. Cohesion is a semantic relationship in the paragraph, which is divided into lexical cohesion and grammatical cohesion. This research aims to identify the grammatical cohesion in Emmanuel Macron’s speech in order to analyze the possibility of using grammatical cohesion. This research uses both theoretical approach (the approach of discourse) and methodological (qualitative descriptive analytical) approach. The data collection is carried out by recording technique. The method of analysis uses the distributional method with BUL (BagiUnsurLangsung) technique. The results are presented by using the method and the formal and informal technique. The analysis resulted in that (1) there are four categories of grammatical cohesion, i.e. reference, substitution, ellipse, and the conjunction (connector), and (2) the personal reference is the dominant category in the speech. The conclusion: the data obtained are 167 references, 4 substitutions, 20 ellipses, 45 conjunctions (connector), and the most dominant is the exosphoric personal reference with the personal pronoun 'we'.